DEEP INTRASLAB DEFORMATION OFFSHORE NORTHERN JAVA REVEALED BY TIME-DOMAIN MOMENT TENSOR (TDMT) INVERSION - Muhammad Nurul Fahmi; Yuni Indrawati; Arie Realita; Madlazim Madlazim (Indonesian Physical Review, 2026)
This study investigates deep-focus intraslab deformation offshore Northern Java by analyzing two recent major earthquakes: 6 July 2020 (  6.67) and 14 April 2023 (  6.96), occurring at centroid depths of ~500–600 km. The objective is to constrain the source mechanisms and infer the prevailing deformation regime within the subducting Indo-Australian slab. We perform time-domain moment tensor (TDMT) inversion of broadband waveforms (GE/GEOFON network) using MTTime, with standard preprocessing (instrument correction and band-pass filtering) and Green’s functions computed from the 1-D ak135 velocity model. Centroid depth is refined via a grid search that maximizes waveform variance reduction (VR). The preferred solutions show good waveform agreement (VR = 82.0% for the 2020 event and 71.6% for the 2023 event) and are consistent with Global CMT solutions (Kagan angles = 7.04° and 6.31°, respectively). Both earthquakes exhibit oblique normal faulting with a persistent dextral strike-slip component, indicating a dominantly extensional stress regime at depth, likely driven by slab pull/gravitational sinking, while the consistent trench-parallel shear suggests more complex internal slab deformation. These results provide quantitative constraints on deep intraslab kinematics beneath Java and motivate expanded event sampling for a more robust regional interpretation.